The Analysis on Ground Treatment Methods Used in East Coast Rail Link (ECRL) Project, Section 6 Maran - AWAIS AZLAN, AWAIS QARNI; Mustapha Kamil Omran; Annuar Abdullah (Progress in Engineering Application and Technology, 2024)
The East Coast Rail Link (ECRL) project is a significant 665-kilometer railway development in Malaysia, aimed at enhancing regional connectivity and economic growth by linking the East Coast states of Kelantan, Terengganu, and Pahang with the Klang Valley on the West Coast. Managed by Malaysia Rail Link Sdn Bhd (MRL) in collaboration with China Communications Construction Company (CCCC), the project faces considerable geotechnical challenges due to the diverse soil conditions along its route, particularly in Section 6, Maran. Effective ground treatment methods are essential to ensure the railway’s stability and longevity. Ground treatment methods improve soil properties to support the infrastructure reliably. This study focuses on addressing the challenges posed by soil compositions in Maran, primarily silty clay, fine sand, and a granite bottom layer. The main objectives include identifying soil behaviour, compiling ground treatment methods like prefabricated vertical drains (PVD) and deep soil mixing (DSM), and propose the most suitable method for the various soil structures encountered. The significance of this research lies in its potential to inform the design and construction of durable and sustainable railway tracks. By providing a comprehensive comparative analysis of ground treatment methods, this study contributes to the development of effective engineering solutions for the ECRL project and offers insights for future geotechnical practices in railway infrastructure.